2017
DOI: 10.1007/s11060-017-2474-0
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial growth factor receptor expression influences 5-ALA induced glioblastoma fluorescence

Abstract: The extent of 5-aminolevulinic acid (5-ALA) guided tumor resection has a determining impact in high-grade glioma and glioblastoma surgery. Yet the intensity of the 5-ALA induced fluorescence may vary within the tumor. We aimed to correlate 5-ALA induced fluorescence with the expression of epithelial growth factor receptor (EGFR) and its constitutively active version EGFRvIII in different glioblastoma (GBM) cell lines. To elucidate the role of EGFR in the metabolism of 5-ALA in GBM cell lines with variable EGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…These findings will however need to be correlated with effective tumor cell infiltration in brain tumor. We have previously demonstrated that different GBM cell lines may have different PpIX signal intensity when treated with the same parameters (7, 16), a phenomenon also described in vivo (21). This phenomenon can be also seen in our mice GBM tumor model, as demonstrated in Figure 7, where tumor not visible to the naked eye with the conventional blue light of the operation microscope, can be made visible with color coded matrix under the Cp9 microscope.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…These findings will however need to be correlated with effective tumor cell infiltration in brain tumor. We have previously demonstrated that different GBM cell lines may have different PpIX signal intensity when treated with the same parameters (7, 16), a phenomenon also described in vivo (21). This phenomenon can be also seen in our mice GBM tumor model, as demonstrated in Figure 7, where tumor not visible to the naked eye with the conventional blue light of the operation microscope, can be made visible with color coded matrix under the Cp9 microscope.…”
Section: Discussionmentioning
confidence: 69%
“…The amount of PpIX in tumor cells is favored by both the activity of cytosolic porphobilinogen deaminase (PBGD) during the replication phase, and by the down-regulation of ferrochelatase (FECH) (6). However, other factors such as protein transporters, tyrosine kinase activity and its downstream effect on hemoxygenase-1 (HO-1), availability of free Fe 2+ -ions and its effect on FECH, are related with PpIX fluorescence (7, 8). Because of the above mentioned factors, the final enhancing results are highly variable and difficult to predict both in clinical and laboratory setting, and might also depend on EGFR expression status in glioma cell lines (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of another ATP-binding cassette transporter known to regulate porphyrin synthesis, ABCB6, has also been shown to increase PpIX accumulation in glioma cell lines and subsequently increase PDT effects [ 63 ]. Epidermal growth factor receptor (EGFR) and EGFRvIII co-expression has been shown to influence 5-ALA fluorescence in GBM [ 64 ]. Additionally, PpIX efflux out of the cell was reported in the presence of fetal bovine serum [ 65 ].…”
Section: Metabolic Activitymentioning
confidence: 99%
“…In the past few years, 5-ALA has been established as an effective intraoperative tool to increase EOR in high-grade gliomas [ 47 ]. Fontana et al found that EGFRvIII activated heme oxygenase-1, thereby reducing the 5-ALA-induced fluorescence staining effect in GBMs [ 19 ]. This study explained the low or absent degree of 5-ALA-induced fluorescence staining in some GBMs.…”
Section: Main Textmentioning
confidence: 99%